IMPERATIVE PRAGMATIC LANGUAGE STUDY IN DAKWAH CONTENT VIDEO ON YOUTUBE - Laeli Qadrianti (LP2M Institut Agama Islam Muhammadiyah Sinjai, 2020)
This paper aims to describe the forms of imperative pragmatic language used by preachers in propaganda content videos. Especially YouTube, this social media is loved by all circles. YouTube social media offers a variety of content, one of which is updated, the video which contains propaganda content. This research method uses descriptive qualitative, data collection is done by listening and recording methods. Data obtained through the method of refer and note then analyzed by classifying and grouping. In the grouping steps are used, namely 1) Data Collection, 2) Data Reduction, 3) Data Display, 4) Data Verification. The results of this study found that there are several forms of imperative pragmatic language contained in the video content of propaganda on YouTube. The imperative pragmatic forms found in the video content of preaching on YouTube, namely, a) pragmatic imperative invitation b) pragmatic imperative petition; c) pragmatic imperative demand; d) imperative pragmatic appeal, e) imperative pragmatic expectation, f) imperative pragmatic recommendation, and g) imperative pragmatic prohibition.